IMPEACHMENT AND CRIME IN THE COSTA RICAN RURAL AREA: THE CASE OF NARANJO (1880-1924) - González Ayala, Eduardo (2014)
This article has as its primary objective to analyze trends related to the complaint and crime increased in Naranjo, a rural town in the period between 1880 and 1924. This period is determined by the application of the penal code of 1880 in Costa Rica, which defining a series of crimes. Research is part of the social history of crime and its development was primary source of the national archives of Costa Rica, as well as the database of such institution, through which it was possible to quantify the complaints that inhabitants of Naranjo made during the designated period. The article demonstrates the increase in complaints regarding offences that were against the material heritage in a time in which it is developing agrarian capitalism, while complaints regarding crimes against the life and honor tended to decrease or remained stable during the period.